Capacity of Caissons in Stiff Over Soft Clay under Combined V-H-M Loadings - Xia, Huxi; Zhou, Xiaowen; Zhou, Mi; Niu, Fujun; Zhang, Xihong (Elsevier, 2021)
This paper carries out a numerical study to investigate the bearing capacities of caissons in stiff-over-soft clay under combined V–H-M loadings. A finite element model is generated and validated with available data in open literature, where a good agreement is obtained. A parametric study is then performed to explore the effects of the upper clay thickness, skirt length, the mobilization of vertical loading and different soil properties on the failure mechanism and corresponding bearing capacity of caissons in stiff-over-soft clay under combined V–H-M loads. The results show that the failure mechanisms of caissons in stiff-over-soft clay are significantly different from those in uniform clay; hence a dramatical distinction between the failure envelopes in stiff-over-soft clay and uniform clay can be found. Last but not the least, based on the numerical results, an empirical design approach is proposed to predict the failure envelopes of caissons under various loading situations.